2002
DOI: 10.1002/pola.10373
|View full text |Cite
|
Sign up to set email alerts
|

Atom transfer radical polymerization of acrylates in an ionic liquid: Synthesis of block copolymers

Abstract: Atom transfer radical polymerization (ATRP) of acrylates in ionic liquid, 1-butyl-3-methylimidazolium hexaflurophospate, with the CuBr/CuBr 2 /amine catalytic system was investigated. Sequential polymerization was performed by synthesizing AB block copolymers. Polymerization of butyl acrylate (monomer that is only partly soluble in an ionic liquid forming a two-phase system) proceeded to practically quantitative conversion. If the second monomer (methyl acrylate) is added at this stage, polymerization proceeds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 29 publications
1
62
0
2
Order By: Relevance
“…5, 22,23 A range of methods has been reported which keeps the catalyst insoluble in the polymerisation phase including the use of fluorous biphase systems, [24][25][26][27] supported catalysts [28][29][30][31] and ionic liquids. [32][33][34][35] A solid supported catalyst can be easily removed, 36,37 but diffusion of reactants to the catalytic site can present a problem. 38, 39 One of us has also explored the use of [N-alkyl-(2-pyridyl)methanimine]copper(I) complexes which had tuneable solubility in certain organic solvents used in this type of polymerisation.…”
Section: Introductionmentioning
confidence: 99%
“…5, 22,23 A range of methods has been reported which keeps the catalyst insoluble in the polymerisation phase including the use of fluorous biphase systems, [24][25][26][27] supported catalysts [28][29][30][31] and ionic liquids. [32][33][34][35] A solid supported catalyst can be easily removed, 36,37 but diffusion of reactants to the catalytic site can present a problem. 38, 39 One of us has also explored the use of [N-alkyl-(2-pyridyl)methanimine]copper(I) complexes which had tuneable solubility in certain organic solvents used in this type of polymerisation.…”
Section: Introductionmentioning
confidence: 99%
“…390 Acrylates were also polymerized successfully in ionic liquids, 391 and the preparation of block copolymers was reported as well. 392 ATRP of acrylates was carried out in chiral ionic liquids, and it was shown that the chirality of the medium affected, although not significantly, the tacticity of the produced polymers. 393 Both copper-and iron-mediated ATRP could be conducted in ionic liquids; in the latter case, no extra ligands were needed to achieve controlled polymerization.…”
Section: Ionic Liquids and Other Solvents Of Low Volatilitymentioning
confidence: 99%
“…[1][2][3] Ionic liquids are organic salts that are liquid at ambient temperatures, containing most commonly ammonium or phosphonium cations and various anions such as simple halide or complex anions (e.g., BF Application of ionic liquids as solvents for radical polymerization, including controlled radical polymerization, has been studied most extensively and some beneficial effects, such as increase of the ratio of propagation to termination rate constants (k p /k t ) leading to improved control in e.g., ATRP of (meth)acrylates have been observed. 4,5 There are also reports on the application of ionic liquids as solvents for cationic polymerization 6,7 but anionic polymerization in ionic liquids has not been reported till now, although in one paper Group Transfer Polymerization (GTP) of methyl methacrylate (MMA) has been described. 8 Anionic polymerization of some vinyl monomers, as shown originally by Szwarc, may proceed as a living process.…”
Section: Introductionmentioning
confidence: 99%